Peningkatan Hasil Belajar Peserta Didik pada Pembelajaran Pendidikan Pancasila Menggunakan Model Cooperative Learning tipe Make a Match di Kelas IV SDN 14 Gadut Kabupaten Agam - Farhan Habib; Zuardi (Journal of Practice Learning and Educational Development, 2025)
This research is based on the results of observations in the field, namely the low learning outcomes of students due to the lack of learning activities that involve students because the learning process is still centered on the teacher, so that students are still less active in the learning process. This research aims to describe how to improve student learning outcomes in science and science learning material on Natural Landscapes and Their Use in Relation to Profession using the Cooperative Learning type Make a Match model in class IV SDN 14 Gadut Agam Regency. This type of research is classroom action research (PTK) using qualitative and quantitative approaches. This research was carried out in two cycles, with research procedures consisting of planning, implementation, observation and reflection. The research data obtained is related to the learning outcomes of the Cooperative Learning type Make a Match model. Data collection techniques include tests and non-tests. The subjects of this research were class teachers as observers, researchers as practitioners or teachers, and 16 class IV students at SDN 14 Gadut Agam Regency. The research results showed that: First, the teaching module for cycle I obtained an average of 89,58% (B), increasing in cycle II to 95,83% (SB). Second, the results of the teacher aspect of learning in cycle I obtained an average of 89,77% (B), increasing in cycle II to 97,22% (SB). Third, the results of the implementation of learning aspects for students in cycle I obtained an average of 89,77% (B), increasing in cycle II to 97,222% (SB). Fourth, the learning outcomes of students in cycle I obtained an average of 74,72 (C), increasing in cycle II to 83,32 (B). This, it can be concluded that the Cooperative Learning type Make a Match model can improve student learning outcomes in science learning in class IV SDN 14 Gadut Agam Regency.